â€œWhat! Is Fanny Ill?â€ - Disease as a Means of Telling the Self in Jane Austenâ€™s Narrative - Daniele, Franca; Biase, Martina Di (European Scientific Journal, ESJ, 2020)
The present paper, placing its focus on three of Jane Austenâ€™s canonical texts: Sense and Sensibility, Pride and Prejudice, and Emma is aimed at evaluating the function of disease states inside the narration. Consequently, the disease state highlights characters, relational and linguistic elements that seem to act as a communicative model that leads up to modifying the social relationships themselves and the fate of the characters. This is the area that is explored in the present paper, utilizing a methodology oriented to shed light, by means of text analysis, on the implications located between those places of the text in which the disease state actively enters and becomes part of the narration. The disease state is able to communicate those most authentic and universal feelings that are at the basis of domestic life narrated in the extraordinary Jane Austenâ€™s microcosm, and as the internal uneasiness is dissolved so is the disease